Veteran and military mental health: the Australian experience. Issue 4 (November 2014) - Forbes, David; Metcalf, Olivia
Abstract : Australia has deployed over 25 000 personnel to recent conflicts in the Middle East and has been involved in peacekeeping missions. Australian veterans report elevated rates of mental health problems such as post-traumatic stress disorder, anxiety disorders, affective disorders and substance use disorders. Veteran healthcare is delivered through publicly funded services, as well as through private services, at primary, secondary and tertiary levels. Some of the challenges involve coordination of services for veterans transitioning from Defence to Veterans' Affairs, service delivery across a large continent and stigma inhibiting service-seeking. Initiatives have been introduced in screening and delivery of evidence-based treatments. While challenges remain, Australia has come a long way towards an integrated and comprehensive approach to veteran mental healthcare.